Immigration Policy and Latinx/é Children from Mixed-Status Families: Mental Health Consequences and Recommendations for Mental Health Providers - Lucila Ramos-Sánchez; Jasmín D. Llamas (MDPI AG, 2024)
The impact of immigration policies on Latinx/é mixed-status families and their children is undeniable. Changes in immigration policy, focused on increased deportation enforcement, within the last three decades have led to an increased fear of deportation and unique circumstances mixed-status families must navigate. These circumstances, combined with fear of deportation, have had deleterious effects on the psychological well-being of the family, in general, and the children, in particular. This paper reviews the impact of immigration policies on Latinx/é mixed-status families, the unique circumstances of mixed-status families, and the mental health implications these have on the children specifically. Articles and books were selected from various sources that addressed Latinx/é mental health, mixed-status families, and immigration. After a review of the literature, these circumstances emerged: familial separation, citizen children second-class citizenry, developmental implications, psychological implications, and coping mechanisms and strategies of mixed-status families. Recommendations for mental health providers who work with children from mixed-status families are provided.